2016
DOI: 10.1039/c6ta04413a
|View full text |Cite
|
Sign up to set email alerts
|

CoOOH ultrathin nanoflake arrays aligned on nickel foam: fabrication and use in high-performance supercapacitor devices

Abstract: A CoOOH/NF ultrathin nanoflake array is fabricated by a facile two-step method. Furthermore, an asymmetric supercapacitor was assembled with CoOOH/NF and reduced graphene oxide, displaying excellent properties as energy storage devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 53 publications
4
23
0
Order By: Relevance
“…The effect of the length of alkyl chain on imidazolium seems to have a quite limited effect since β3-pH↗(IL 2C), β3-pH↗(IL 6C) and β3-pH↗(IL 10C) have rather comparable SSA values (256, 246 and 232 m 2 /g respectively), even if the general tendency is that the shorter the alkyl chain on imidazolium ring, the higher the SSA. Such elevated SSA values for polycrystalline cobalt oxyhydroxide are among the highest ever reported in the literature, along with those of Wen et al (241 m 2 /g) [8,12,15,21,[41][42][43]. Similarly, porosity is greatly influenced by the experimental conditions, as illustrated in Figure 4b-d, which compares the pore size distribution between all materials.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The effect of the length of alkyl chain on imidazolium seems to have a quite limited effect since β3-pH↗(IL 2C), β3-pH↗(IL 6C) and β3-pH↗(IL 10C) have rather comparable SSA values (256, 246 and 232 m 2 /g respectively), even if the general tendency is that the shorter the alkyl chain on imidazolium ring, the higher the SSA. Such elevated SSA values for polycrystalline cobalt oxyhydroxide are among the highest ever reported in the literature, along with those of Wen et al (241 m 2 /g) [8,12,15,21,[41][42][43]. Similarly, porosity is greatly influenced by the experimental conditions, as illustrated in Figure 4b-d, which compares the pore size distribution between all materials.…”
Section: Resultssupporting
confidence: 68%
“…In all these applications, a high specific surface area is required to optimize the electrode/electrolyte interface and/or the reactivity of the electrode material as the overall performances strongly depend on surface reactions. Several synthesis approaches have been reported in the literature, leading to nanostructured cobalt oxyhydroxides with various morphologies, such as nanoflakes, nanorods, nanosheets, nanodiscs, thin films, or even as single crystals [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Most of the time, the nanostructuration strategy consists of adding an electronic conductive carbon source or to grow cobalt oxyhydroxide on a (porous) support; however, few works have investigated the synthesis parameters that influence nanostructuration [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For both nanohybrids, the curves reveal two main redox peaks during the oxidation processes, the rst one at 0.014 V and the second at 0.46-0.47 V which may respectively be assigned to the Co(II)/ Co(III) and Co(III)/Co(IV) redox processes. 25,27 These peaks are displaced to lower potential compared to bare HCoO 2 for which the rst peak is at 0.19 V and the second at 0.52 V (see ESI S3 †). 26 These displacements of redox potentials, most probably caused by the surface modication by the ionic liquids, allow shiing the Co(III)/Co(IV) oxidation potential inside the electrochemical windows of 5 M-KOH, leading to a higher peak current and higher charge capacity.…”
Section: Electrochemical Performancesmentioning
confidence: 99%
“…[22][23][24] Among all these electrode materials, non-stoichiometric layered cobalt oxyhydroxide (HCoO 2 ) offers a two dimensional structure suitable for fast ionic diffusion as well as a good intrinsic electronic conductivity due the high oxidation state of cobalt, which favors electron transportation. 25,26 While the HCoO 2 pristine material usually exhibits a specic capacitance between 130 and 140 F g À1 in KOH electrolytes at 1 A g À1 , 27,28 different strategies were investigated to improve its electrochemical performances. For example, C. J. Raj et al focused on nano-structuration by developing a hydrothermal synthesis to get HCoO 2 nanorods with a specic capacitance of 177 F g À1 at 5 mV s À1 , 29 whereas Zhu et al developed HCoO 2 / CNT (carbon nanotube) hybrids 27,30 giving 270 F g À1 and 312 F g À1 at 1 A g À1 .…”
Section: Introductionmentioning
confidence: 99%
“…This type of material has a nonstoichiometric composition with a layered structure and a good electric conductivity due to the high oxidation states of transition metal cations, which are beneficial for fast electron and electrolyte ion transportation. For example, it is reported that CoOOH has a conductivity of 5 S cm -1 [102]. With proper synthetic strategies, CoOOH can reach a considerably high specific capacity and a long term cycling stability of over 10 000 cycles.…”
Section: Transition Metal Hydroxidesmentioning
confidence: 99%